2020
DOI: 10.3390/met10020191
|View full text |Cite
|
Sign up to set email alerts
|

Laser Polishing of Ti6Al4V Fabricated by Selective Laser Melting

Abstract: Selective laser melting (SLM) is emerging as a promising 3D printing method for orthopedic and dental applications. However, SLM-based Ti6Al4V components frequently exhibit high roughness values and partial surface defects. Laser polishing (LP) is a newly developed technology to improve the surface quality of metals. In this research, LP is applied to improve the surface finish of components. The results show that the laser beam can neatly ablate the aggregates of metallic globules and repair cracks and pores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Finally, the reduced porosity in the laser-polished layer increases the hardness and density of the material. Many articles 12,48,52 have similar reports. Li et al 52 found that the microhardness was 426 HV, which was about 25% higher than the as-received sample (340 HV), as shown in Fig.…”
Section: Microhardnessmentioning
confidence: 67%
See 3 more Smart Citations
“…Finally, the reduced porosity in the laser-polished layer increases the hardness and density of the material. Many articles 12,48,52 have similar reports. Li et al 52 found that the microhardness was 426 HV, which was about 25% higher than the as-received sample (340 HV), as shown in Fig.…”
Section: Microhardnessmentioning
confidence: 67%
“…To obtain a high precision machined surface, it is necessary to optimize the process parameters. Liang et al 12 and Zhou et al 48 experimentally studied the relationship between the laser polishing process parameters of Ti6Al4V alloy and the surface quality and finally obtained the optimal combination of process parameters. Table 1 summarizes the surface roughness of laser polished Ti6Al4V alloy and lists the optimum process parameters corresponding to the surface roughness.…”
Section: Surface Morphology and Roughnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Titanium alloy (Ti–6Al–4V) samples produced using selective laser melting (SLM) technology have been widely studied over the years. [ 1–6 ] The effects of heat treatment on the mechanical properties and microstructure of Ti–6Al–4V parts have been widely investigated. [ 7 ] Moreover, the significant effects of heat treatment and specimen building direction on the dynamic behavior of SLM produced Ti–6Al–4V have also been reported.…”
Section: Introductionmentioning
confidence: 99%